2020
DOI: 10.1088/1475-7516/2020/02/004
|View full text |Cite
|
Sign up to set email alerts
|

A tip for landscape riders: multi-field inflation can fulfill the swampland distance conjecture

Abstract: We study how both the swampland distance conjecture and the Lyth bound affect the parameter space of multi-field models of inflation. A generic feature of multi-field inflation is that the geodesic distance [∆φ] G separating any two points laying along the inflationary trajectory differs from the non-geodesic distance [∆φ] NG traversed by the inflaton between those points. These distances must respect a relation of the formwhere f is a function determined by the specific multi-field model under scrutiny. We sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 100 publications
(163 reference statements)
1
24
0
Order By: Relevance
“…Otherwise a tower of light states emerges which would spoil the low energy effective description. A recent discussion on multifield inflation and the DSC has appeared in [40]. So here we simply stress that inflationary trajectories with large turning rates Ω/H 1 differ strongly from a geodesic and thus (2.36) does not apply.…”
Section: Fat Inflation and The Swamplandmentioning
confidence: 90%
“…Otherwise a tower of light states emerges which would spoil the low energy effective description. A recent discussion on multifield inflation and the DSC has appeared in [40]. So here we simply stress that inflationary trajectories with large turning rates Ω/H 1 differ strongly from a geodesic and thus (2.36) does not apply.…”
Section: Fat Inflation and The Swamplandmentioning
confidence: 90%
“…Usually in the curved field manifold the inflaton trajectory may demonstrate turning dynamics (or equivalently non-geodesic motion in the field space). It has also been suggested that such kind of multi-field behaviour may be free from some possible problems faced by single field inflation [56][57][58]. Moreover, richer phenomenology emerges in this class of multi-field models, which could be interesting for future observational detections.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that if the background cosmology for single field inflation is not GR based, then this inflationary regime can still satisfy the swampland criterion [30][31][32][33][34]. Multi field inflationary models are consistent with the conjectures even in GR based paradigms [35]. It's also worth noting that in both GR and non-GR based cosmologies, the warm inflation paradigm has been shown to be very compatible with the swampland criterion even for single field models [36][37][38][39][40] The recently proposed "Trans Planckian Censorship Conjecture" (TCC) [41] is another swampland conjecture that has sparked a lot of interest in inflationary cosmology .…”
Section: Introductionmentioning
confidence: 84%